1981
DOI: 10.1128/jcm.13.1.115-119.1981
|View full text |Cite
|
Sign up to set email alerts
|

Chemically defined medium for Legionella pneumophila growth

Abstract: A chemically defined medium containing 18 amino acids, inorganic salts, rhamnose, choline, and ferric pyrophosphate has been developed. The final concentrations of salts and amino acids were modeled after yeast extract. This medium supported the growth of four serogroups of Legionella pneumophila. Growth in shake cultures at 37 degrees C produced a lag time of approximately 5 h and a generation time of 4 h with a maximum growth yield of 10 9 colony-forming units per ml. A soluble brown pigment was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 4 publications
1
61
1
Order By: Relevance
“…Moreover, determination of the intracellular growth rate by gentamicin kill assay demonstrated ,1000-fold increased bacterial numbers within 48 h, suggesting a generation time of at least ,5 h that was similar to other Proteobacteria, e.g. Rickettsia spp., Anaplasma marginale or Legionella pneumophila ranging from 4 to 17 h (Hidalgo, 1975;Ristroph et al, 1981;Pang and Winkler, 1994). Therefore, B. henselae can be considered as a facultative intracellular pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, determination of the intracellular growth rate by gentamicin kill assay demonstrated ,1000-fold increased bacterial numbers within 48 h, suggesting a generation time of at least ,5 h that was similar to other Proteobacteria, e.g. Rickettsia spp., Anaplasma marginale or Legionella pneumophila ranging from 4 to 17 h (Hidalgo, 1975;Ristroph et al, 1981;Pang and Winkler, 1994). Therefore, B. henselae can be considered as a facultative intracellular pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Legionella pneumophila relies on amino acids as the main source of energy and carbon, although carbohydrates may be a minor substrate (George et al, 1980;Ristroph et al, 1981;Tesh and Miller, 1981;Eylert et al, 2010). Even though L. pneumophila preferentially utilizes amino acids for carbon and energy, in silico analysis of the L. pneumophila genome sequence revealed that this organism is auxotrophic for the seven amino acids Arg, Cys, Ile, Leu, Met, Thr and Val (Cazalet et al, 2004;Chien et al, 2004).…”
Section: Amino Acid Requirements Of L Pneumophilamentioning
confidence: 99%
“…Even though L. pneumophila preferentially utilizes amino acids for carbon and energy, in silico analysis of the L. pneumophila genome sequence revealed that this organism is auxotrophic for the seven amino acids Arg, Cys, Ile, Leu, Met, Thr and Val (Cazalet et al, 2004;Chien et al, 2004). Furthermore, it has been shown that the amino acids Arg, Cys, Ile, Leu, Met, Ser, Thr and Val are essential for growth of L. pneumophila in vitro (Pine et al, 1979;George et al, 1980;Reeves et al, 1981;Ristroph et al, 1981;Tesh and Miller, 1981;Tesh et al, 1983;Molofsky and Swanson, 2004;Wieland et al, 2005;Eylert et al, 2010). The four amino acids, Arg, Cys, Gln and Ser, are needed to support growth in vivo (Wieland et al, 2005).…”
Section: Amino Acid Requirements Of L Pneumophilamentioning
confidence: 99%
See 2 more Smart Citations